FACTORS OF DEVELOPMENT OF HEPATORENAL SYNDROME - Mukhammadieva M.I. (Modern American Journals, 2025)
Hepatorenal syndrome (HRS) is a type of acute kidney injury (AKI), occurring in patients with decompensated liver cirrhosis and is associated with high mortality. We aim to describe the predictors associated with the development of HRS in cirrhotic patients with AKI. We retrospectively analyzed 125 cirrhotic patient encounters with AKI across all Health institutions between 1 January 2019 and 31 December 2022. We performed multivariate analyses to determine independent predictors of development of HRS. Alcoholic cirrhosis was the most common identified etiology of cirrhosis. The mean Model for End-Stage Liver Disease Scorewas18 (±7).
Keywords: predictors, hepatorenal syndrome, cirrhosis, mortality, acute kidney injury